Traditional Poetic Series Related to Detail Motivating to Enlighenment - Oybek Barziyev (Researchparks Publishing, 2021)
The article In discusses about the Fergana Valley poets of the Uzbek literature of the age of national awakening: Hamza Hakimzadeh Niyazi, Samarbonu, and Dilshodi Barno, the article discusses traditional features and one poetic type nourished by the concepts of stimulating people to enlightenment.